THE INFRRIORITY VIEW TO THE STANDARD ARABIC LANGUAGE - Dr . Muhammad Abdel Salem Jabara (Journal of College of Education, 2023)
Arabic language is one of the living languages that still challenges the variables of time and its developments. However, this language was not far from those who have animosity towards it and lay in wait for it. Therefore, the research aims to determine the state of Classical Arabic language from a historical perspective, its strengths, weaknesses, and how it dominated over languages for a long period of time. Then, it presented the stage of decline and its negative effects on the language, leading to its low position among languages to the point where it is looked at with a condescending view. This resulted in a sense of defeatism among Arab citizens, objecting to the reasons throughout its long history, and presenting some observations that can improve its reality and elevate it to its rightful place among languages.
Keywords: condescending view, Orientalism, media